The I/Indian Not-In-The-Textbook: Native/Indigenous Post-Structuralism, Critical Methodologies, Epistemologies, and Tribal Realities as Agency toward the Decolonization of the Territorial Divide In American Indian Studies Courses - Alan Lechusza Aquallo, (Indian Journal of Management and Language (IJML), 2024)
This article focuses upon how, within American Indian Studies courses, there is a necessary border crossing between territorialized Native and non-Native students. Taking the literal borders of Indian reservations, and repositioning these realities as a metaphor for critical epistemological deconstruction, I argue that there is a necessary educational border crossing which is necessary for Native/Indigenous equity and socio-political justice to be realized and acquired as cultural currency. As students within these courses begin to understand, embrace, and challenge American Indian Studies (AIS) courses, and the dynamics of the discipline, there is a self-defined border crossing between, and within, the Native/Indigenous ideological territories, and literal, physical reservation borders, which the curriculum represents. Each student may – or will – find their own point of critical Native/Indigenous inquiry, from which they are challenged and welcomed to embrace, as well as depart from previous scripted Euro American rhetorical references regarding Native/Indigenous cultures. Following this critical epistemology, for the student participant, a new territory of knowledge, cultural, and expressed understanding from, and about, Native/Indigenous Peoples becomes manifest; a new academic frontier is possible. Applying this methodology, for academic decolonization, the i/Indian image/icon need not exist within the textbook(s); the potential for recognizing and decolonizing the physical reservation borders becomes possible. The realities of Native lives – both historic and contemporary – do matter, beyond these limitations and scripted inclusions within textbooks. Whereas a text may prove as a site of disenfranchisement, inequity, and, tribal marginalization, there, then, lies the necessity for Native V/voices to be heard, reviewed, and function as sovereign references and expressions, which advances beyond the terminal reservation borders as agency. This article seeks to challenge pre-determined academic references, mis-representations and re-presentations of Native Peoples, read: the i/Indian image/icon, as well as providing a critique of how Native/Indigenous realities are, then, able to sovereignly relate to the large non-Native population beyond the limitations of a physical reservation border. Taking note that there is no one single educational methodology, which can be applied within American Indian courses, multiple academic perspectives begin to surface, which address the educational process about Native Peoples. The 3 views of Indian education – anthropological/archeological/ethnographic/historical,sympathetic, activist – as I argue, become, and are maintained as antiquated points of articulation, which continue to be employed about Native Peoples, replacing the active dynamics of Native cultures, customs, traditional knowledge, and expressions. This article, therefore, challenges these 3 views of Indian education – anthropological/archeological/ethnographic/historical, sympathetic, activist – noting that the classroom, textbook(s), and their references, mis-representations and re-presentation(s) about Native Peoples, need to be decolonized, following the importance, ideology, dialectics and dynamics of tribal sovereignty, equity, and socio-political justice.